An integrated remediation approach using combinations of biochar, Rhizobium leguminosarum, and Vigna radiata for immobilizing and dissipating cadmium contaminants from the soil–mustard plant system - Hira, Qurat-ul-Ain Ali; Mahboob, Midhat; Azhar, Rimsha; Munir, Faiza; Gul, Alvina; Hayat, Asim; Shah, Tariq; Amir, Rabia (Frontiers in Plant Science, 2023)
Cadmium (Cd) contamination in our environment is a potential concern, as it harms food crops that influence human health. The co-combinations of Biochar (BC), Vigna radiata (VR) as inter-cropped and Rhizobium leguminosarum (RL) is a conclusive approach to reduce the immobilization of cadmium from soil to mustard plant (Brassica juncea). Mustard plant is a food and oil production crop that has been consumed worldwide, however, this plant has the properties of hyperaccumulation thus, it stored Cd that can be a part of the food chain. Hence, it is crucial to reduce the Cd accumulation in mustard plants to make them reliable for food consumption. To improve soil sorption capacity and immobilization efficiency, wheat husk biochar was mixed with RL microbe and intercropped with mustard plants for further investigation. Sampling was performed at an early stage (30 days) and maturity stage (60 days) to determine cadmium's impact on the morpho-physiological attributes of plant. Data analysis was conducted through Two ways- ANOVA followed by the Post Hoc Tukey HSD test concluded that co-combined effectively improved plant traits from 65-90%. However, six combinations (BC+RL+VR) proved the most effective results and reduced the translocation of Cd in mustard plants by 70-95%. In post-harvesting soil analysis through XRD identified an undetectable Cd in soil. Thus, it gives us clear confirmation that these approaches can lead to well-defined cadmium soil remediation. Moreover, this study provides insight info on different morpho-physiological attributes’ responses toward cadmium stress in mustard plants and would aid to develop cadmium stress tolerance in the mustard plant.